Self-instructional modules on taxation for grade six fast learners - Mañgalindan, Luningning F. (College of Education, University of the Philippines Diliman, 1975)
The study focused on the use of modular instruction or methodology in teaching taxation/tax consciousness among Grade VI fast learners for more knowledge and skills. Self-instructional materials, specifically the module as utilized in the study, composed of a sequence of materials carefully ordered and organized to assure the best learning conditions for the learner. The modules utilized the principles of reinforcement to make certain that learning does occur. Findings of the study showed that instructional innovation is an alternative approach to the ever-increasing and uncontrollably accumulating facts which become a problem and a burden to the teacher.